A STUDY OF THE CHARACTERISTICS OF ENTREPRENEURS IN THE DEVELOPMENT OF AUTOMATION AND ROBOT SYSTEMS TOWARDS BUSINESS OPERATIONS - Tresirichod, Teetut (RMUTT Global Business and Economics Review, 2021)
The objectives of this research are as follows: 1) To study the characteristics of entrepreneurs in the development of automation and robots 2) To study the business operations of the entrepreneur in the development of automation and robots 3) To study the characteristics of entrepreneurs in the development of robot automation systems that influence the business of entrepreneurs. This research is quantitative research, by using survey research methods and using questionnaires as a tool to collect data. The study sample consisted of 80 entrepreneurs in the development of automation and robotics. The statistics used in the data analysis were frequency and percentage. The investigator used stepwise multiple regression analysis. The results showed that Characteristics of entrepreneurs in the development of automation and robotics consist of 12 characteristics: integrity, knowledge, individuality, passion for success, innovation, commitment to patience, creativity, risk-taking, self-confidence, Executive ability, learning from experience, and responsibility Overall, automation and robotics entrepreneurs most agree. It was found that the business operations of entrepreneurs in the development of automation and robotics in 6 areas financial situation, meeting customer needs, earning commitment from employees, creating quality products and services, promoting innovation and creativity, and social responsibility. Characteristics of automation and robotics entrepreneurs that influence the business of automation and robotics entrepreneurs. found that the integrity, knowledge, individuality, passion for success, commitment to patience, and risk-taking affect the business operations, statistically significant at the .05 level.